An exploratory study of treated-bed nets in Timor-Leste: patterns of intended and alternative usage - Lover, Andrew A.; Sutton, Brett A.; Asy, Angelina J.; Wilder-Smith, Annelies (Malaria journal, 2011)
The Timor-Leste Ministry of Health has recently finalized the National Malaria Control Strategy for 2010-2020. A key component of this roadmap is to provide universal national coverage with long-lasting insecticide-treated nets (LLINs) in support of achieving the primary goal of reducing both morbidity and mortality from malaria by 30% in the first three years, followed by a further reduction of 20% by end of the programme cycle in 2020 [1]. The strategic plan calls for this target to be supported by a comprehensive information, education and communication (IEC) programme; however, there is limited prior research into household and personal usage patterns to assist in the creation of targeted, effective, and socio-culturally specific behaviour change materials.